DESCOPERIRI MONETARE MEDIEVALE DIN CAMPANIA ARHEOLOGICĂ 2020 DE LA REMETEA MARE (JUD. TIMIȘ) – PUNCTUL GOMILA LUI GABOR - Raoul Șeptilici; Octavian C. Rogozea; Dorel Micle (Analele Banatului. Arheologie-Istorie, 2022)
During preventive archaeological excavations in the area of Remetea Mare commune (Timiș County) in 2020, several medieval vestiges came to light, including nine coins (all silver alloy): Banat of Severin - Nicolae Redwitz (1429-1435?), 1 coin (coin no. 1), Hungary - Wladislav I (1440-1444) 2 coins (coins no. 2-3), Iancu of Hunedoara (1446-1453), 3 coins (coins no. 4-6), Matia Corvin (1458-1490), 2 coins (coins no. 7-8), Ferdinand I (1526-1564), 1 coin (coin no. 9). The preventive research from August-September 2020 completed the series of research in the perimeter of Remetea Mare-2/Gomila lui Gabor site, where several areas were excavated in the late 70s and early 80s of the 20th century. The coins enrich the repertoire of findings of this kind and establish, with high accuracy, a date for the medieval cemetery where they were uncovered.